Study of differences in neighborhood satisfaction regarding gender - Esperidião, Aline Ramos (2021)
There is growing evidence that the interaction between the individual and the urban environment has results in satisfaction. Several publications address residential satisfaction, however,there are few studies in Brazil on urban factors that influence it from a gender perspective. In this sense,the question is: are the satisfaction perceptions of men and women in relation to the completeneighborhood different? Thus, the objective of this research is to understand if there are differences in the perception of neighborhood satisfaction in relation to the individual's gender, and what they are. The research adopted the survey method for data collection, and multivariate analysis as a data analysistechnique. A questionnaire was designed, collecting 316 from the South, Southeast and Midwest regionsof Brazil. Thirty-seven variables related to the urban environment and neighborhood satisfaction wereselected, with gender as the discriminating variable. In general, neighborhood satisfaction among men isrelated to the existence of cultural activities, good commerce and parking spaces. For women, it isrelated to other factors, such as good schools, the appearance of the surroundings and safety. Theresearch contributes to a better understanding of the needs of men and women in urban areas.